PERAN DAN FUNGSI BADAN PERWAKILAN DESA DALAM PENETAPAN KEBIJAKAN DI DESA BONGAN KABUPATEN TABANAN - Ni Luh Gede Astariyani; Made Nurmawati; Anak Agung Sri Utari; Ayu Putu Laksmi Danyanthi (Universitas Mataram, 2023)
The role of the Village Consultative Body (BPD) in formulating village policies. Policy in the village is the basis when the local government will implement its policy. Policies in the village are for example in the form of Village Regulations (Perdes) in Bongan Village, Tabanan District, Tabanan Regency. The methods used in the training are presentation, discussion and practice. Presentations are carried out only as an introduction to the material and to provide knowledge about certain materials. Furthermore, more activities carried out with discussion and practice. The approach used is experiential learning, so that the lecturer is more of a facilitator, and the participation of participants can be maximized. Through this experience-based training participants are actively involved in every activity. The conclusions from the results of the research above are (1) The role of the Consultative Body in Bongan Village, Tabanan District, Tabanan Regency in carrying out the oversight function of Village Regulations has not been implemented optimally (2) The biggest inhibiting factors in the implementation of BPD supervision of Village Government Bongan, Tabanan District, Tabanan Regency are: The role of the BPD is not well understood and the understanding of the duties and functions of the BPD in administering Village Government, as well as other factors, such as mental attitude, and existing customary/family factors.